2015
DOI: 10.3126/kumj.v12i2.13653
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Graft Dislocation After Thoracic Aortic Endovascular Repair

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…1,2 Although migration of thoracic grafts was specifically defined in 2010, 2 there is a lack of structural data reported from real-life registries regarding late migration. 3,4 The purpose of this study was therefore to describe the incidence and timing of stent graft migration and to identify potential risk factors for migration to allow further optimization of a follow-up protocol after TEVAR.…”
mentioning
confidence: 99%
“…1,2 Although migration of thoracic grafts was specifically defined in 2010, 2 there is a lack of structural data reported from real-life registries regarding late migration. 3,4 The purpose of this study was therefore to describe the incidence and timing of stent graft migration and to identify potential risk factors for migration to allow further optimization of a follow-up protocol after TEVAR.…”
mentioning
confidence: 99%
“…However, these rates were observed with first-generation devices, different methods of assessment of endograft position, and diverse definitions of EM. 6,22,23 After publishing the definition of EM in 2010, trials using contemporary endografts reported improved TEVAR performance with EM rates up to 8%. 5,19,24 However, very few trials used the standard-based protocol of assessment of endograft position, which includes primary analysis of centerline distances between tips and covered parts of the endograft relative to large aortic branches and secondary analysis relative to anatomical landmarks (eg, calc, surgical clips, etc), when endograft movement >10 mm was suspected.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, literature and evidence on this clinically important topic remain limited. 5,6 The majority of related studies failed to analyze EM perstandard and reported heterogeneous EM rates using diverse assessment methods and definitions. Furthermore, reported EM-related reintervention and morbidity/mortality rates vary widely between studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early and late migration of the aortic stent graft is discussed previously. 3 4 5 Anatomic factors (e.g., type of aortic arch) and procedural factors (the type of proximal landing zone) can also influence the migration of stent grafts. However, there is not much evidence in the literature regarding the incidence and risk factors for stent-graft migration.…”
Section: Introductionmentioning
confidence: 99%